Colloidal-like aggregation of a functional amyloid protein. Issue 40 (9th October 2020) - Azulay, David N.; Ghrayeb, Mnar; Ktorza, Ilanit Bensimhon; Nir, Ido; Nasser, Rinad; Harel, Yair S.; Chai, Liraz
Abstract : TasA, a bacterial functional amyloid protein, aggregates in a colloidal – like mechanism upon exposure to acidic conditions. Abstract : Functional amyloid proteins are self-secreted by microbial cells that aggregate into extracellular networks and provide microbial colonies with mechanical stability and resistance to antibiotic treatment. In order to understand the formation mechanism of functional amyloid networks, their aggregation has been studied in vitro under different physical conditions, such as temperature, salt concentration, and pH. Typical aggregates' morphologies include fibers or plaques, the latter resembling amyloid aggregates in neurodegenerated brains. Here, we studied the pH-reduction-induced aggregation of TasA, an extracellular functional amyloid appearing as fibers in biofilms of the soil bacterium, Bacillus subtilis . We used turbidity and zeta potential measurements, electron microscopy, atomic force microscopy, and static light scattering measurements, to characterize the aggregates of TasA and to compare them with colloidal aggregates. We further studied the aggregation of TasA in the presence of negatively charged nanoparticles and showed that nanoparticles co-aggregated with TasA, and that the co-aggregation was hindered sterically. Based on these studies, we concluded that, similarly to colloidal aggregation, TasA aggregation occurs due to surface potential modulations and that the aggregation is followed by a rearrangement process. Shedding light on the aggregation mechanism of TasA, our results can be used for the design of TasA aggregation inhibitors and promoters.